Keeping a tight leash on education - Abd Razak, Dzulkifli (2008)
HIGHER education in Malaysia is certainly growing. This is evident with the establishment of more than 500 private institutions in the country. They offer a wide variety of programmes leading to diplomas and degrees. All this was made possible with the Private Higher Educational Institutions Act (1996). This allowed private higher education institutions to be established in a relatively liberal way. This led to the introduction of a variety of programmes to attract more school leavers to pursue tertiary education in view of the limited places in public universities.